2016
DOI: 10.1177/1321103x16676649
|View full text |Cite
|
Sign up to set email alerts
|

Assessmentaslearning in music education: The risk of “criteria compliance” replacing “learning” in the Scandinavian countries

Abstract: Recent reforms in England and the USA give evidence that teaching methods and content can change rapidly, given a strong external pressure, for example through economic incentives, inspections, school choice, and public display of schools’ and pupils’ performances. Educational activities in the Scandinavian countries have increasingly become dominated by obligations regarding assessment and grading. A common thread is the demand for equal and just assessment and grading through clear criteria and transparent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
11
0
4
Order By: Relevance
“…En annan aspekt av kursplanens uppbyggnad är den styrande funktion som kunskapskraven i Lgr 11 förefaller ha fått. Enligt en forskningsstudie inverkar detta på vilket innehåll som privilegieras i undervisningen (Ferm Almqvist, Vinge, Väkevä & Zandén, 2016). I skapande musikaliska aktiviteter ligger att resultaten inte kan vara förutsedda, vilket också innebär att de är svåra att bedöma och betygsätta utifrån på förhand givna mål (Higgins & Mantie, 2013;Johansen, Holdhus, Larsson & MacGlone, 2019).…”
Section: Inledningunclassified
“…En annan aspekt av kursplanens uppbyggnad är den styrande funktion som kunskapskraven i Lgr 11 förefaller ha fått. Enligt en forskningsstudie inverkar detta på vilket innehåll som privilegieras i undervisningen (Ferm Almqvist, Vinge, Väkevä & Zandén, 2016). I skapande musikaliska aktiviteter ligger att resultaten inte kan vara förutsedda, vilket också innebär att de är svåra att bedöma och betygsätta utifrån på förhand givna mål (Higgins & Mantie, 2013;Johansen, Holdhus, Larsson & MacGlone, 2019).…”
Section: Inledningunclassified
“…Ett exempel på översiktsfråga skulle kunna vara: "vilka problem kan uppstå när formativ bedömning ligger till grund för genomförande av undervisning?" Inom området finns det ett växande antal fallstudier som uppmärksammar att användningen av formativ bedömning kan ge upphov till vad Torrance (2007) benämner som "bedömning som lärande" (se också Hume & Coll, 2009;Ferm Almqvist, Vinge, Väkevä & Zandén, 2016;Torrance, 2012). Torrance (2007) använder beteckningen "bedömning som lärande" för att beskriva hur formativ bedömning kan ge upphov till instrumentella undervisningskulturer, där synliggörandet av mål och kriterier förefaller att prägla elevernas lärandeerfarenheter på bekostnad av ämnesinnehållet (jfr Hume & Coll, 2009).…”
Section: Forskningens Roll I Praktikenunclassified
“…In a qualitative study of three purposely selected elementary music teachers, Salvador (2011) noted that participants viewed the number of students taught, time constraints, and the lack of administrator support as being obstacles to improved assessment. Similarly, Harrison et al (2013), Lehman (2008), and Ferm Almqvist et al (2017) all echoed the concern over class size issues and their impact on effective assessment. Russell and Austin (2010) also found that administrative guidance or assistance with assessment was rare, yet when administrators provided help, nonmusic assessments were less likely to be present in the classroom.…”
Section: What Challenges Occur In Music Assessmentmentioning
confidence: 99%
“…Logistical challenges may also influence assessment decisions and impede improvement in assessment practice (Ferm Almqvist, Vinge, Väkevä, & Zandén, 2017; Harrison et al, 2013; Russell & Austin, 2010; Salvador, 2011). In a qualitative study of three purposely selected elementary music teachers, Salvador (2011) noted that participants viewed the number of students taught, time constraints, and the lack of administrator support as being obstacles to improved assessment.…”
Section: What Challenges Occur In Music Assessmentmentioning
confidence: 99%